2020
DOI: 10.1111/tbed.13699
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating the risk of African swine fever virus in feed with anti‐viral chemical additives

Abstract: African swine fever (ASF) is currently considered the most significant global threat to pork production worldwide. Disease caused by the ASF virus (ASFV) results in high case fatality of pigs. Importantly, ASF is a trade-limiting disease with substantial implications on both global pork and agricultural feed commodities. ASFV is transmissible through natural consumption of contaminated swine feed and is broadly stable across a wide range of commonly imported feed ingredients and conditions. The objective of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…The efficacy of both MCFA and aqueous formaldehyde has been experimentally confirmed for ASFV. In Niederwerder et al (2020), MCFA (1:1:1 ratio of C6, C8, and C10) and aqueous formaldehyde (Sal CURB ® ) were investigated for their ability to inactivate or reduce the infectivity of ASFV in cell culture and in feed under a transoceanic shipment model [ 94 ]. In cell culture, dose–response curves were determined by adding MCFA or aqueous formaldehyde at various inclusion rates (0.03–2.0%) to a standard volume of ASFV; titration assays were performed to quantify ASFV remaining post-exposure to liquid additives.…”
Section: Chemical Mitigation Methods For Asfv In Feedmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of both MCFA and aqueous formaldehyde has been experimentally confirmed for ASFV. In Niederwerder et al (2020), MCFA (1:1:1 ratio of C6, C8, and C10) and aqueous formaldehyde (Sal CURB ® ) were investigated for their ability to inactivate or reduce the infectivity of ASFV in cell culture and in feed under a transoceanic shipment model [ 94 ]. In cell culture, dose–response curves were determined by adding MCFA or aqueous formaldehyde at various inclusion rates (0.03–2.0%) to a standard volume of ASFV; titration assays were performed to quantify ASFV remaining post-exposure to liquid additives.…”
Section: Chemical Mitigation Methods For Asfv In Feedmentioning
confidence: 99%
“…ASFV-contaminated ingredients were mixed with either MCFA (1.0% inclusion) or aqueous formaldehyde (0.33% inclusion) during the 30-day model simulating shipment conditions. Although all treated feed ingredients maintained detectable ASFV DNA on PCR, results demonstrated reduced ASFV infectivity post-treatment, with most MCFA-treated feed ingredients (16/18) and all formaldehyde-treated feed ingredients (18/18) lacking infectious ASFV at the conclusion of the study [ 94 ]. Under the conditions of these studies, both MCFA-and formaldehyde-based feed additives demonstrated efficacy in a dose-dependent manner for reducing ASFV infectivity and show potential as mitigation tools for reducing the risk of ASFV introduction and transmission through feed.…”
Section: Chemical Mitigation Methods For Asfv In Feedmentioning
confidence: 99%
“…The half-life of viable ASFV was found to be between four and 14 days in various feed matrices under simulated intercontinental transit time-temperature profiles [30–32]. In a related study, ASFV-spiked feed was found to have the virus titre reduced by around 1.3 log 10 cycles after being subjected to a 30 day trans-Atlantic transport temperature simulation [33].…”
Section: African Swine Fever Virus: the Role Of The Environmentmentioning
confidence: 99%
“…Importantly, the data also support that GML as a feed additive can reduce ASFv infectivity in feed environments. Further exploration of additional MCFA mixtures alone or together with GML and other monoglycerides is warranted, especially since recent findings show that another carrier-free MCFA mixture can inhibit ASFv in feed [52] and that MCFA and GML blends can exhibit synergistic phospholipid membranedisruptive activities [53]. Continued development of suitable formulations to maximize the antiviral performance and industrial utility of MCFA and GML for water and feed delivery [54] could help these additives become important tools in combating the infection and spread of swine viral pathogens, including ASFv.…”
Section: Discussionmentioning
confidence: 99%